Increasing of C/N ratio with addition of tapioca starch in Oligochaetes culture substrate - Hadiroseyani, Yani; Puspitasari, Ardina; Budiardi, Tatag (Indonesian Society of Scientific Aquaculture (ISSA), 2015)
ABSTRACT This study was aimed to improve the productivity of sludge worm (Oligochaetes) in culture systems using the addition of tapioca flour to the substrate to increase C/N ratio up to 10, 20, and 30. The substrate used was a mixture of mud and chicken manure with a ratio of 1:1 on the container measuring 100×12×15 cm3. Culture system used was a recirculation system. Initial stock of the worm was at density 150 g/m2. Results showed the highest population and biomass of the worm in each treatments was occurred on tenth day. The highest density of sludge worm, i.e. 421,145 ind/m2 with total biomass of 1,497.80 g/m2, was obtained on the treatment of C/N ratio at 20 (P <0.05). Keywords: Oligochaetes, C/N ratio, tapioca starch, recirculation system ABSTRAK Penelitian ini bertujuan untuk meningkatkan produktivitas cacing sutra (Oligochaeta) pada sistem budidaya dengan memperbaiki kualitas substrat cacing menggunakan penambahan tepung tapioka sehingga mencapai rasio C/N 10, 20, dan 30. Substrat yang digunakan yaitu campuran lumpur tanah dan kotoran ayam dengan perbandingan 1:1 pada wadah budidaya berukuran 100×12×15 cm3. Sistem budidaya yang digunakan yaitu sistem resirkulasi. Cacing dibudidayakan pada padat penebaran 150 g/m2. Hasil menunjukkan puncak populasi dan biomassa cacing sutra terjadi pada hari kesepuluh. Kepadatan cacing tertinggi, yaitu 421.145 ind/m2 dengan biomassa 1.497,80 g/m2, diperoleh pada perlakuan penambahan tepung tapioka dengan C/N rasio 20 (P<0,05). Kata kunci: cacing sutra, rasio C/N, tepung tapioka, sistem resirkulasi